Relationships between Vitamin B12, Folate Levels and Clinical Features in Attention Deficit Hyperactivity Disorder and Attention Deficit Hyperactivity Disorder-Not Otherwise Specified - Yusuf Öztürk; Zehra Topal; Nuran Demir; Ali Evren Tufan (Journal of Pediatric Research, 2020)

(untitled)
Aim:In this study, we aimed to compare the levels of vitamin B12 and folate in children with Attention Deficit and Hyperactivity Disorder (ADHD) and Attention Deficit and Hyperactivity Disorder-Not Otherwise Specified (ADHD-NOS).Materials and Methods:This study was planned as a cross-sectional, retrospective study. Patients were recruited between January 2012 and January 2013 and 205 case records were evaluated. The ADHD and ADHA-NOS groups were compared according to vitamin B12 and folate levels. Symptom severity was evaluated by the Turgay DSM-IV-Based Child and Adolescent Behavior Disorders Screening and Rating scale. Anxiety symptom severity was assessed by The Screen for Anxiety Related Emotional Disorders.Results:The average age of the children in the ADHD group was 10.88±3.02 (n=99) years, and the average age of the children in the ADHD-NOS group was 9.93±2.49 (n=106) years. There was no statistically significant difference between two groups in terms of Vitamin B12 level and folate level (p>0.05). A statistically significant negative correlation between the total number of diagnoses of a child and vitamin B12 levels was found. Folate levels correlated significantly with anxiety total scores generalized anxiety subscale.Conclusion:Vitamin B12 levels may be affected in children with impairing ADHD symptoms and increased comorbidities. The results of the study should be supported by future studies.